The Effect of Principal Clinical Supervision Strategy on Teachers’ Pedagogic Competence in SMP Negeri 22 Tanjung Jabung Timur - Wahyuningsih, Sri Wulan (FKIP Universitas Jambi, 2025)
This study aims to analyze and describe in depth how the clinical supervision strategy implemented by the Principal at SMP Negeri 22 Tanjung Jabung Timur affects the improvement of teachers’ pedagogic competence. The primary focus is on understanding the processes, challenges, and outcomes of clinical supervision to improve the quality of learning. This study uses a qualitative case-study design. The primary data collection techniques include participant observation, in-depth interviews (with the principal, supervised teachers, and other teacher representatives), and document analysis (supervision instruments, learning implementation plans, and notes on classroom observation results). Data were analyzed using qualitative techniques, namely interactive models: data reduction, data presentation, and conclusions drawn. The results of the study show that implementing a systematic, collaborative, and sustainable clinical supervision strategy significantly influences teachers’ pedagogical competence. The most effective strategies involve pre-observation (setting of focus and goals), classroom observation (objective data collection), and post-observation (reflective discussion and establishment of individual follow-up plans). The primary influence is manifested in improving teachers’ abilities in: (1) formulating specific learning objectives, (2) managing classroom interaction and student motivation, and (3) conducting formative and summative evaluations. It was also found that a supportive professional relationship between the Principal and the teacher is the key to the successful implementation. From the results of this study, it can be concluded that clinical supervision is an effective managerial instrument for the professional development of teachers. It is recommended that Principals strengthen their role as mentors and facilitators, and provide adequate time and resources to ensure the consistent implementation of clinical supervision cycles.